Analysing conceptions of social justice in the European Union - Adams, Zoe Louise (Florence, 2015)
"This paper draws on findings from a broad research project that employed a constructionist approach in analysing policy-discourse in the EU. It uses sources produced by the European Commission between 1958 and 2015 for this purpose. The research is used as the basis from which to analyse how the EU’s conception of social justice has hanged over time. The paper analyses two periods in detail, namely 1958 – 1979 and 2010 – 2015 to illustrate the nature of the change that has taken place.